Activities of the Oxazolidinones Linezolid and Eperezolid in Experimental Intra-Abdominal Abscess Due to Enterococcus faecalis or Vancomycin-Resistant Enterococcus faecium - Schülin, T. (American Society for Microbiology, 1999)
The in vivo effectiveness of oxazolidinones eperezolid (U-100592) and linezolid (U-100766) against one strain each of Enterococcus faecalis and vancomycin-resistant Enterococcus faecium was examined in a rat model of intra-abdominal abscess. MICs of both drugs were 2 μg/ml for each strain. At doses of 25 mg/kg of body weight twice daily intravenously or orally, linezolid produced small but statistically significant reductions in abscess bacterial density for E. faecalis. The reduction in viable cells observed would not likely be clinically relevant. Eperezolid was ineffective at this dose. At a dosage of 100 mg/kg/day, linezolid treatment led to an approximately 100-fold reduction in viable cells per gram of abscess. Against E. faecium infections, intravenous eperezolid and oral linezolid were effective, reducing densities approximately 2 log(10) CFU/g. Both oxazolidinones demonstrated activity against enterococci in this model. However, results were modest with the dosing regimens employed.